PENGARUH EKSTRAK BUAH NANAS (Ananas comosus) TERHADAP KUALITAS TEPUNG KULIT PISANG KEPOK (Musa paradisiaca formatypica) SEBAGAI SUMBER BELAJAR BIOLOGI SMA - Ivan Wibisono; Achyani Achyani (Bioedukasi Jurnal Pendidikan Biologi, 2013)
Citric acid as a preservative function, inhibit oxidation and kill the bacteria. Naturally of  citric acid is found in many fruits such as pears, oranges and pineapple. Banana peel waste is one that still has enough good content to be processed and be utilized. The purpose of this research/study to determine there is influence of pineapple extract toward the quality of banana peel flour. This study uses the method completely randomized design (CRD), with one control and three treatments with eight repetitions. A data obtained by the test Liliefors normality test, homogeneity with bartlette test and continued to test the hypothesis. The conclusion is found that the influence of the quality of the flour extract of pineapple and banana skin treatment using extracts of pineapple 1000 ml give the best effect. Based on this study can be used as resources in the learning of Science Process Skills alternative approach .Kata kunci: Ekstrak buah nanas, kualitas tepung kulit pisang kepok